Modulation of Cytoskeleton, Protein Trafficking, and Signaling Pathways by Metabolites from Cucurbitaceae, Ericaceae, and Rosaceae Plant Families - Ankit Patel; Aliyah Rasheed; Isiah Reilly; Zil Pareek; Mattia Hansen; Zayn Haque; Daniela Simon-Fajardo; Chloe Davies; Akash Tummala; Karlyn Reinhardt; Alexandria Bustabad; Maxwell Shaw; et al. (MDPI AG, 2022)
One promising frontier within the field of Medical Botany is the study of the bioactivity of plant metabolites on human health. Although plant metabolites are metabolic byproducts that commonly regulate ecological interactions and biochemical processes in plant species, such metabolites also elicit profound effects on the cellular processes of human and other mammalian cells. In this regard, due to their potential as therapeutic agents for a variety of human diseases and induction of toxic cellular responses, further research advances are direly needed to fully understand the molecular mechanisms induced by these agents. Herein, we focus our investigation on metabolites from the Cucurbitaceae, Ericaceae, and Rosaceae plant families, for which several plant species are found within the state of Florida in Hillsborough County. Specifically, we compare the molecular mechanisms by which metabolites and/or plant extracts from these plant families modulate the cytoskeleton, protein trafficking, and cell signaling to mediate functional outcomes, as well as a discussion of current gaps in knowledge. Our efforts to lay the molecular groundwork in this broad manner hold promise in supporting future research efforts in pharmacology and drug discovery.